The coexistence between GDPR and blockchain - Teixeira, N.; Coutinho, C. (Proceedings of the 15th China-Europe International Symposium on Software Engineering Education (CEISEE 2019), 2019)
The constant evolution of technology sometimes cannot avoid its conflict with the corresponding evolution of its surrounding regulations and legislation. This article is a Position Paper that highlights the discrepancy between the Blockchain architectural design and its inherent apparent incompatibility with the standing European directives concerning General Data Protection Regulation (GDPR). As Blockchain-based solutions emerge and their adoption increases, the concerns about current regulation regarding storage of personal data and the conciliation with the Blockchain’s model arises.